Investigation of Disorder Factors in Relation to Mental Toughness of South Sumatera Karate Athletes - Kumbara, Hengki; Sari, Puput Sekar; Rizhardi, Rury (Universitas PGRI Palembang, 2024)
Abstract The aim of this research is to investigate and find out whether there is a relationship between mental toughness and disturbance factors in South Sumatran karate athletes. The method used is the correlation method. The population is the projected 21 Aceh-North Sumatra PON athletes. The sample was taken from the total population, namely 21 athletes. Data collection uses psychological tests, namely mental toughness psychological tests before being connected to variables, and mental toughness psychological tests after being connected to internal and external variables. The number of valid questions was 18 questions with a reliability level above 0.607 with a strong relationship. Data analysis is parametric analysis of partial and simultaneous correlation tests. The research results showed that several factors were found that interfered with athletes' mental toughness due to internal and external factors. The relationship between internal factors and mental toughness in South Sumatra Karate athletes is low because the correlation coefficient value is 0.103, while the contribution of implementation is 11%. The relationship between external factors and mental toughness in South Sumatran Karate athletes is strong because the correlation coefficient value is 0.607 while the contribution of implementation is 61%. There is a simultaneous relationship between internal and external factors and mental toughness in South Sumatran Karate athletes with a fairly strong correlation coefficient level of 0.569 with an application contribution of 59%.